The Reading Grannies: Modelling How to Teach Reading - Stewart, Sandra Lilian; Modiba, Maropeng (Journal of Interdisciplinary Studies in Education, 2019)
This paper reports on an intervention intended to develop literacy amongst learners in a rural, state farm school situated in Kwa-Zulu Natal (KZN), South Africa. The principal and teachers in the school invited a group of volunteers, who named themselves the “Reading Grannies” into the school to model how to read an English text. The assumption was that listening to English read by first-language (L1) speakers, would expose learners to, for example, pronunciation, tone and expression and convey meaning better. In addition, both teachers and learners who were non-primary English speakers would develop an ear for the language and this would, in turn, help teachers to improve their teaching of English.